Irises - Stork, Francisco X. (Arthur A. Levine Books, 2012)
Kate, eighteen, and Mary, sixteen, must make some adult decisions about the course their lives should take when their loving but old-fashioned father dies suddenly, leaving them with their mother, who has been in a persistant vegetative state since an accident four years earlier.